2009
DOI: 10.3233/jad-2009-1033
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Paradox in Alzheimer's Disease: It Does Not Prevent Loss of Cognition and May Even Be Detrimental

Abstract: There is controversy as to whether vitamin E is beneficial in Alzheimer's disease (AD). In this study, we tested if vitamin E prevents oxidative stress and loss of cognition in AD. Fifty-seven AD patients were recruited and divided in two groups: placebo or treated with 800 IU of vitamin E per day for six months. Of these 57 patients, only 33 finished the study. We measured blood oxidized glutathione (GSSG) and used the following cognitive tests: Mini-Mental State Examination, Blessed-Dementia Scale, and Clock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
140
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(146 citation statements)
references
References 40 publications
1
140
0
2
Order By: Relevance
“…This is the case for vitamin E as some meta-analyse have concluded that supplementation with high doses may increase mortality [62][63][64] . Our work has suggested that administering an antioxidant and following changes in cognition is not sufficient as there are patients whose antioxidant status does not change after administration of antioxidant vitamins [59] . It seems that dietary antioxidants are safer but contribute very poorly to improve cognition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the case for vitamin E as some meta-analyse have concluded that supplementation with high doses may increase mortality [62][63][64] . Our work has suggested that administering an antioxidant and following changes in cognition is not sufficient as there are patients whose antioxidant status does not change after administration of antioxidant vitamins [59] . It seems that dietary antioxidants are safer but contribute very poorly to improve cognition.…”
Section: Discussionmentioning
confidence: 99%
“…In those in whom it does not (non-respondent) vitamin E results in an even more pronounced loss of cognition than in patients treated with a placebo. For the patients who experimented a reduction in oxidative stress, cognition was maintained or slightly improved in the six months of the duration of the study [59] .…”
Section: Polyphenols Flavonoids and Herbal Supplementsmentioning
confidence: 99%
“…However, experimental result proved that, the inhibition of plasminogen activator inhibitor 1 reduces the level of plasma and Aβ oligomers levels from the brain in transgenic animals [43]. Other studies indicated that, Aβ oligomers clearance is mediated by the hormonal peptide somastotatin by the action of nephrilysin [44].…”
Section: Amyloid Clearancementioning
confidence: 99%
“…There were excluded: studies in vitro, animal models, pharmacological studies, plasma nutrient level measurement, metabolism of nutrients in the physiopathology of AD, nutritional status or food intake in people with dementia; review articles, systematic reviews, monographies, books and chapters of books, however, they were utilized as literature reference to identify other studies that possibly meet the criteria. From the 182 selected studies for examination of full texts, Included studies in the systematic review are characterized in Table 4 (range: 66.5-81.6 y), except for two studies that did not make this data available (192,193).…”
Section: Study Identificationmentioning
confidence: 99%
“…Studies with missing data not provided by authors (193,259,(259)(260)(261) or evaluating similar outcomes in the same population and intervention were excluded from analysis (199,213,215). Data analyses show the following results.…”
Section: Intervention Effectsmentioning
confidence: 99%